2021
DOI: 10.3897/pharmacia.68.e66065
|View full text |Cite
|
Sign up to set email alerts
|

The management of upper gastrointestinal symptoms: A study on community pharmacies in Italy

Abstract: Upper gastrointestinal (GI) symptoms are usual complaints among patients presenting to Italian community pharmacies. However, information on treatment history of those patients is often lacking. This descriptive, cross-sectional study aims at exploring the medication history of individuals with upper GI tract symptoms visiting one of the 20 enrolled community pharmacies, over a period of 7 months, based on the administration of a questionnaire. Of 1,020 interviewees, 62.1% had asked for a medical consultation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…In addition, the age inclusion criterion of 35–65 years enabled us to target those most likely to experience symptoms suggestive of FD. 4 , 8 The survey questions were not formally validated. However, the way questions were asked, including the provision of categorical answer options to respondents, has been used and tested for robustness and stability in several other similar studies conducted by Bayer within the past 2 years.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, the age inclusion criterion of 35–65 years enabled us to target those most likely to experience symptoms suggestive of FD. 4 , 8 The survey questions were not formally validated. However, the way questions were asked, including the provision of categorical answer options to respondents, has been used and tested for robustness and stability in several other similar studies conducted by Bayer within the past 2 years.…”
Section: Discussionmentioning
confidence: 99%
“… 2 , 3 A recently published cross-sectional survey of Italian community pharmacies found that among 1020 individuals suffering from at least one common gastrointestinal symptom, 12% reported postprandial fullness, 10% upper abdominal bloating, and 7% epigastric pain. 4 …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations